y=(x+y)(3c-k)

Simple and best practice solution for y=(x+y)(3c-k) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=(x+y)(3c-k) equation:


Simplifying
y = (x + y)(3c + -1k)

Multiply (x + y) * (3c + -1k)
y = (x(3c + -1k) + y(3c + -1k))
y = ((3c * x + -1k * x) + y(3c + -1k))
y = ((3cx + -1kx) + y(3c + -1k))
y = (3cx + -1kx + (3c * y + -1k * y))
y = (3cx + -1kx + (3cy + -1ky))

Reorder the terms:
y = (3cx + 3cy + -1kx + -1ky)
y = (3cx + 3cy + -1kx + -1ky)

Solving
y = 3cx + 3cy + -1kx + -1ky

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3cy' to each side of the equation.
-3cy + y = 3cx + 3cy + -1kx + -3cy + -1ky

Reorder the terms:
-3cy + y = 3cx + 3cy + -3cy + -1kx + -1ky

Combine like terms: 3cy + -3cy = 0
-3cy + y = 3cx + 0 + -1kx + -1ky
-3cy + y = 3cx + -1kx + -1ky

Add 'ky' to each side of the equation.
-3cy + ky + y = 3cx + -1kx + -1ky + ky

Combine like terms: -1ky + ky = 0
-3cy + ky + y = 3cx + -1kx + 0
-3cy + ky + y = 3cx + -1kx

Reorder the terms:
-3cx + -3cy + kx + ky + y = 3cx + -1kx + -3cx + kx

Reorder the terms:
-3cx + -3cy + kx + ky + y = 3cx + -3cx + -1kx + kx

Combine like terms: 3cx + -3cx = 0
-3cx + -3cy + kx + ky + y = 0 + -1kx + kx
-3cx + -3cy + kx + ky + y = -1kx + kx

Combine like terms: -1kx + kx = 0
-3cx + -3cy + kx + ky + y = 0

The solution to this equation could not be determined.

See similar equations:

| =y(x+y)(3c-k) | | b=(x+y)(3c-k) | | 90n=1/2 | | 2a^3+3a^3+a^4= | | a-ax-2xa-3a-3= | | 81/2*2/1= | | 26=-8/5y | | (6x+36)(x^2-6x-7)=0 | | -4/9f=-3 | | 80/4800=x/6600 | | 8=-2/5c | | 3+3y-6=(x+y)+1 | | 3(7-5t)= | | 3/4g=-12 | | 3x-27=9+7x | | 14/6=63/t | | 2/24=x/84 | | =10y-4 | | =8y | | 2x+14*17=13 | | z+3/5=z/2 | | =6x | | 7x^2+25x-12=18-4x | | -10=-b/4 | | 5(m+5)/6(m+1) | | 2.9n+1.7=3.5+2.3 | | 6x^2+33x+36=0 | | 3a+8=35 | | 7d+2e-3d-7e= | | 7/8/x=14 | | 4x^3+3x^2-6x=0 | | -16n^2+12n=0 |

Equations solver categories